Agroinfiltration of Lycopersicon Esculentum Using Luria Bertani Broth Medium on Wounded Leaves - Lok, Angela Siew Foong (unnimas, 2010)
Tomato, Lycopersicon esculentum is a potential model plant for the studies on transient expression of foreign gene. The main objective of this project is to transform the plant leaves using agroinfiltration technique onto wounded leaves with LB medium as an infiltration medium. Agroinfiltration was carried out by injecting the Agrobacterium tumefaciens directly into wounded tomato leaves to allow transformation of gene to occur. Germination of tomato seed was done first followed by the preparation of Agrobacterium tumefaciens that carries pBI121 plasmid. Transformation of the young leaves was later then carried out, leaving it 3 to 7 days after the infiltration to allow integration of gene to occur. Analysis of putative transformants by using Polymerase Chain Reaction (PCR) has successfully amplified the sequence of gus gene with the size of 600 bp at 10X and 20X dilution of DNA template. It was reported that young leaves aged 5-8 weeks which has been injected with LB medium gave a better result as compared to the IMtreated leaves.